Genetic Analysis of Vibrio parahaemolyticus O3:K6 Strains That Have Been Isolated in Mexico Since 1998. - Abraham Guerrero; Marcial Leonardo Lizárraga-Partida; Bruno Gómez Gil Rodríguez; Alexei Fedorovish Licea-Navarro; Valeria Jeanette Revilla-Castellanos; Irma Wong-Chang; Ricardo González-Sánchez (PLoS ONE, 2017)
Vibrio parahaemolyticus is an important human pathogen that has been isolated worldwide from clinical cases, most of which have been associated with seafood consumption. Environmental and clinical toxigenic strains of V. parahaemolyticus that were isolated in Mexico from 1998 to 2012, including those from the only outbreak that has been reported in this country, were characterized genetically to assess the presence of the O3:K6 pandemic clone, and their genetic relationship to strains that are related to the pandemic clonal complex (CC3). Pathogenic tdh+ and tdh+/trh+ strains were analyzed by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Also, the entire genome of a Mexican O3:K6 strain was sequenced. Most of the strains were tdh/ORF8-positive and corresponded to the O3:K6 serotype. By PFGE and MLST, there was very close genetic relationship between ORF8/O3:K6 strains, and very high genetic diversities from non-pandemic strains. The genetic relationship is very close among O3:K6 strains that were isolated in Mexico and sequences that were available for strains in the CC3, based on the PubMLST database. The whole-genome sequence of CICESE-170 strain had high similarity with that of the reference RIMD 2210633 strain, and harbored 7 pathogenicity islands, including the 4 that denote O3:K6 pandemic strains. These results indicate that pandemic strains that have been isolated in Mexico show very close genetic relationship among them and with those isolated worldwide.